통합 멀티캐스팅 환경에서 효율적인 그룹 통신에 관한 연구 - 김현주(Hyun-jue Kim); 남정현(Jung-hyun Nam); 김승주(Seung-joo Kim); 원동호(Dong-ho Won) (韓國컴퓨터情報學會論文誌, 2005)
Through the increment of group oriented application services, the multicast communication in wire/wireless network has become a widely discussed researching topic. However solution for security, efnciency and scaleability of a multicast communications are not enough to be satisfactory. Tn this paper, we Propose a new secure, efficient and scalable multicasting protocols to provide a integrated multicast service. Our protocol is an authenticated key establishment protocol which has been designed specifically for use with low powered computationally weak equipment such as Cellular phone and PDA(Personal Digital Assistant). 최근 그룹 지향적 응용 서비스가 증가함에 따라 유?무선 네트워크상에서 사용 가능한 멀티캐스트 통신에 대한 연구가 활발히 진행되고 있다 그러나 멀티캐스트 통신에 대한 안전성과 효율성에 대한 해결책은 아직 미비한 상태이다. 본 논문에서는 유?무선 통합 멀티캐스트 서비스지원을 위해, 인증을 제공하는 안전한 멀티캐스팅 프로토콜을 제안한다. 제안하는 프로토콜은 개인 휴대단말기 등과 같은 낮은 연산 처리 능력을 가지는 시스템에서 사용 가능한 효율적인 프로토콜이다